POINT TO POINT: AN ALTERNATIVE METHOD FOR EXTRACTING “HOMOLOGOUS POINTS” IN BATHYMETRIC DATA COLLECTED WITH A MULTIBEAM SYSTEM - Ferreira, Ítalo Oliveira; Oliveira, Júlio César de; Santos, Afonso de Paula dos; Silva, Arthur Amaral e; Medeiros, Nilcilene das Graças (Boletim de Ciências Geodésicas, 2022)
Due to waterway transport efficiency, mainly for commercial trades, the use of sea/river routes has grown recently. So, the importance of producing high quality nautical charts stands out. A nautical chart is the hydrographic survey final product and its accuracy depends on data quality collected, primarily of the vertical quality (depth). In this sense, despite the theoretical and practical difficulty in obtaining homologous points in hydrographic surveys, even when performing check lines, bathymetric data must always be delivered with a statistically proven confidence level. Thus, this study has two main objectives: i) to propose a method, called Point to Point (P2P), for obtaining “homologous points” for hydrographic surveys carried out with multibeam systems, without resorting to mathematical and/or statistical interpolations, called Point to Point (P2P); ii) to quantify the magnitude of the difference between the statistical evaluation using check lines (CL) and by overlapping successive sounding lines (SL), applying the P2P method. The results showed that P2P is easy to application, provide low computation effort, is robust and consistent. Besides that, was possible to applied successive regular lines to get a validation of the hydrographic survey.